Baseline Serum C-Reactive Protein Level Predicts Mortality in Cryptococcal Meningitis. (29th October 2020) - Chesdachai, Supavit; Engen, Nicole W; Rhein, Joshua; Tugume, Lillian; Kiiza Kandole, Tadeo; Abassi, Mahsa; Ssebambulidde, Kenneth; Kasibante, John; Williams, Darlisha A; Skipper, Caleb P; Hullsiek, Kathy H; Musubire, Abdu K; et al.
Abstract: Background: C-reactive protein (CRP) is an acute phase protein produced by the liver in response to systemic inflammation. CRP is a helpful surrogate biomarker used for following the progression and resolution of infection. We aimed to determine the association of baseline CRP level and the temporal change in CRP over time with cryptococcal meningitis outcome. Methods: We reviewed 168 prospectively enrolled HIV-infected Ugandans with confirmed first-episode cryptococcal meningitis. Baseline plasma CRP collected within 5 days of meningitis diagnosis was categorized into quartiles. We compared baseline CRP with 18-week survival using time-to-event analysis. Results: Of 168 participants, the baseline first quartile of serum CRP was <29.0 mg/L, second quartile 29.0–49.5 mg/L, third quartile 49.6–83.6 mg/L, and fourth quartile >83.6 mg/L. Baseline CD4 count, HIV viral load, and cerebrospinal fluid results did not differ by CRP quartile. Participants with CRP >49.5 mg/L more likely presented with Glasgow Coma Scale (GCS) <15 ( P  = .03). The 18-week mortality rate was 55% (46/84) in the highest 2 quartile CRP groups (>49.5 mg/L), 41% (17/42) in the mid-range CRP group (29.0–49.5 mg/L), and 14% (6/42) in the low-CRP group (<29.0 mg/L; P  < .001). After adjustment for possible confounding factors including GCS <15, CRP remained significantly associated with mortality (adjusted hazard ratio, 1.084 per 10 mg/L; 95% CI, 1.031–1.139; P  = .0016). Conclusions: Higher baseline CRP is associated with increased mortality in HIV-infected individuals with first-episode cryptococcal meningitis. CRP could be a surrogate marker for undiagnosed coinfections or may reflect immune dysregulation, leading to worse outcomes in persons with advanced AIDS and concomitant cryptococcal meningitis.